Penyelesaian Soal Limit Fungsi Trigonometri dengan Solusi Cepat pada siswa SMA - Iin Ariyanti; Nafisa Nur Zaqiyah (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
The purpose of this service is to help students deal with the shortage of time when working on multiple choice math problems, especially in the trigonometric function limit material. This activity was carried out on April 24, 2019 at SMAN 1 Tamban, Barito kuala, South Kalimantan, attended by 25 students as participants. The implementation of this activity consists of opening and introduction, explanation and application of problem solving, then practice questions and gift giving, as well as closing and group photos. The material for the quick solution of trigonometric function limit problem solving consists of trigonometric limits using the spruck rules, trigonometric limits using the delete rules of "evil" cosines, and trigonometric limits using the "good" cosine change rules. In the midst of community service activities, the service team appealed to students to prioritize understanding of mathematical concepts in solving mathematical problems. Quick solutions are recommended to be used only on multiple choice tests and force students to solve problems in a short time. Overall, this activity went well and smoothly and without significant obstacles.